The Contribution of Transformative Pedagogy to the Learning Space of Scholars: A Case of South African Universities - The Contribution of Transformative Pedagogy to the Learning Space of Scholars: A Case of South African Universities (E-Journal of Humanities, Arts and Social Sciences)
This paper interrogates the contribution of transformative pedagogy and digitalized platforms to the rekindled learning space of scholars. The paper was motivated by diverse discourses and notions on the role which transformative pedagogy and digitalized platforms could play in bringing about a stimulating learning space for scholars. The paper is both conceptual and empirical in nature within the qualitative research paradigm. Interviewing techniques and documents review were employed to generate data for the paper. Research findings reveal that firstly, a transformative pedagogy with digitalized platforms encourage the development of reflective knowledge base. Secondly, they promote critical consciousness and agency within scholars. Thirdly, they encourage the engagement of scholars through participatory instructional methods. Fourthly, they make schooling a fun instead of being a burden. Fifthly, they recognise schooling inequalities and attempt to promote social justice. Lastly, a transformative pedagogy with digitalized platforms resist coercive relations of power between scholars and their lecturers. In conclusion, a transformative pedagogy with digitalized platforms prepare scholars of the 21st century to harmonise the world of schooling and the outside world of life. The researcher recommends for the embracing of a transformative pedagogy and digitalized platforms in education by virtue of them promoting an activist pedagogy that combines constructivist and critical pedagogy. The other recommendation relates to supporting the transformative pedagogy with digitalized platforms to persist to facilitate scholars to critically examine their beliefs, values and knowledge. The study emphasizes how transformative pedagogy is useful at tertiary institutions especially during tough times such as Covid-19.